Air Pollution as a Risk Factor for Increasing Hospitalizations of Preschool Wheeze in Hong Kong - Ka-Ka Siu; Chin-Pang Wong; Rachel Shui-Ping Lee; Jack Pak-Yeung Chan; Shuk-Yu Leung; Eric Yat-Tung Chan; Ka-Li Kwok; Ada Yuen-Fong Yip; Rupert Phillips; Daniel Kwok-Keung Ng (Pediatric Respirology and Critical Care Medicine)
Background: Wheeze has been reported to affect one-third of preschoolchildren. While different wheeze patterns have been shown to predict future asthma risk, limited data are available on the risk factors for preschool wheeze in Asia. Methods: Preschool children admitted to hospitals through emergency departments for wheeze, from 2004 to 2015 in Hong Kong, were retrospectively identified. Potential risk factors for admissions over the same period were retrieved (i.e., air pollutants, preterm delivery, and maternal age). Results: A total of 46,258 patients meeting the inclusion criteria were identified during the 12-year period. The preschool wheeze admission rate increased by 34% over the past 12 years, with an average year-on-year rise of 4.2%. Environmental nitrogen dioxide (NO2) concentration was significantly associated with an increase in admission for preschool wheeze (r = 0.63, P = 0.028). Univariate regression analysis was performed on potential risk factors. Annual average NO2concentration (P = 0.007) and maternal age more than 40 years (P = 0.012) were significant risk factors. For multivariable regression analysis, annual average NO2concentration (β = 0.18, 95% confidence interval = 0.06–0.30) was the only independent factor associated with preschool wheeze admission. Conclusions: The increase of NO2concentration is a significant risk factor for the increase in hospitalizations for preschool wheeze in Hong Kong.